Analisis Manajemen Risiko pada UMKM “Bolu Pisang dan Brownies Chantiqa” Cimahi - Watini, Putri; Nurbaeti Amien, Neneng (Jurnal Serambi Ekonomi dan Bisnis, 2024)
Micro, Small and Medium Enterprises (MSMEs) in Indonesia, especially in the culinary sector, are growing rapidly but are also not free from challenges and opportunities. This research aims to analyze the risk management of MSMEs producing banana cake and brownies. The method used was qualitative through direct interviews with MSMEs Bolu Pisang and Brownies Chantiqa Cimahi. The research results show that the most significant risks include raw material, financial, operational, HR and marketing risks. To overcome this risk, MSMEs are advised to implement product diversification strategies, maintain the quality of raw materials, and conduct market analysis. This research contributes to the development of better risk management in this business, so that it can increase the resilience and competitiveness of businesses in the market. Based on the results of the SWOT analysis, the strength of this Chantiqa sponge cake is in terms of taste. The weakness is the weather factor, if it is the rainy season it causes the room temperature to become humid. The opportunity for this business is product development. And the threat to this business is competitors with similar products.